Relationship between proposition and situation in the English proverbs with secondary meaning - Shakunova, Nataliya S. (Journal of the Belarusian State University. Philology, 2020)
The research is carried out on the material of the proverbs of the English language, based on metaphorization. This article is devoted to the description of the operation of the semantic and syntactic mechanism in the formation of secondary meanings in the proverbs of the English language. A procedure for studying the secondary meaning within the framework of the theory of compositional syntax is proposed. First, the denotative aspect of the semantics of the sentence is studied, and a conclusion is made about the relationship between participants in situations in proverbs with metaphorization. Then the significative aspect of the semantics of sentences is analyzed and the main characteristics (direction and dynamism) of the relations between the arguments of the proposition are determined, after which, by superimposing of these two aspects of semantics, the regularities of the relationship between the proposition and the situation are revealed and the possibilities of metaphorizing the individual lexical components of the sentence, as well as metaphorizing the entire sentence, or the entire proverb. On the basis of this, a conclusion is made about the semantic and syntactic mechanism of metaphorization of an argument (arguments), the predicate and the predicate-argument structure. The interrelation of the semantic and syntactic mechanisms is analyzed, and a conclusion is made about how the choice of semantic units affects the syntactic structures used, and vice versa.
Keywords: compositional syntax; proposition; situation; significative aspect; denotative aspect; metaphorization; object in a proposition; participant in a situation